Pengaruh Gaya Hidup Konsumtif dan Promosi Penjualan Terhadap Pembelian Impulsif Makanan Kekinian Mahasiswa Urban Surabaya - Tamara Virsa Putri; Sri Setyo Iriani (Jurnal Ilmu Manajemen, 2020)
Surabaya is the capital of the Indonesian province of east java and the second most populous city plus metropolitan area in Indonesia after Jakarta with 3.158.943 citizens recorded in the 2019 census. Surabaya citizen does not only consist of indigenous people who settled in Surabaya but also people outside the city who urbanized to Surabaya. The city is highly urbanized with industries centralized in the city, one sector that is urbanized to Surabaya aside the labor sector is from the education sector. Surabaya has a variety of reputable state and private campuses that serve as a destination for students from various regions to pursue their education. Urbanization conducted by urban students makes their lifestyle more consumptive with the facilities and easy access in Surabaya. One of them is the easy access to the famous food in every corner of the city with various sales promotions (discounts and cashback) offered by marketers to stimulate purchases by urban students. The changes in lifestyle and the various sales promotion stimulate urban students to make impulsive purchases. In this study, the population is 100 respondents. The result of the study revealed that a consumptive lifestyle has a significant effect on impulse buying so that urban students with a consumptive lifestyle tend to make more impulsive purchases. While the variable sales promotions dont have a significant effect on impulse buying which means that the promotions by the outlet do not affect the impulsive buying decision of urban students.